Gender, age, farm and slaughter month factors affecting dairy carcass traits and the relationship between the traits, thoracic cavity depth, and carcass length - Thawonwat, R.; Sivapirunthep, P.; Kongpiboon, W.; Tuntivisoottikul, K. (International Journal of Agricultural Technology, 2020)
Farm affected most traits, except for the thoracic cavity depth (TCD), skin weight (SKW) and percentage of skin weight (PSK). Slaughter month had affected all the traits, except for PSK. The relational study, findings showed that the final live weight had highly significant positive correlated with all studied traits (P<0.01), except for TCD and PSK. Hot carcass weight had highly significant positive correlated with dressing percentage of carcass length (CL) and SKW (P<0.01), except for PSK. Dressing percentage did not correlate with TCD and CL. However, the negative correlation between TCD and CL (r = -0.325) was found, whereas the TCD had no correlation with SKW and PKW. However, CL had negative correlation with PSK (r=-0.287), while the relationship between SKW and PSK was 0.586.